SOUNDCLOUD APPLICATION: CAN IT ENHANCE THE STUDENTS’ LISTENING COMPREHENSION? - Putra, Nandadewa Aji; Prastikawati, Entika Fani; Setyorini, Ajeng (English Language Teaching Methodology, 2024)
English is essential to learn in today’s world, with numerous methods available for effective acquisition. First English skill that learners’ have to master is listening. Although listening is the first skill to master, however it is challenging to teach English listening in class. Due to the difficulty of teaching English listening, teacher starting to implementing teaching media to teach English. This research aims is to investigate whether using SoundCloud application can enhances students’ listening comprehension. By involving tenth-grader students,72 participant that divided into experiment and control group. Pre-test and Post-test are uses to collect the data. After the data was gathered, the data analyzed via SPSS 26. The result of this study revealed that SoundCloud can improve the students’ listening comprehension. This result was derived from the data that experimental group has higher achievement in listening comprehension rather than control group. To conclude, SoundCloud application is an alternative tool to be implemented in the listening comprehension session.  Additionally, SoundCloud does not only provide an enjoyable way to teach English listening but also significantly boost the students' listening comprehension